PENTINGNYA LITERASI MEMBACA DAN MENULIS PADA SISWA KELAS I SD SEBAGAI FONDASI PEMBELAJARAN LANJUTAN - Yrmina, Yrmina Damayanti; B. Widharyanto; Setya Tri Nugraha; R. Kunjana Rahardi; Yuliana Setyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading and writing literacy were the main foundations for successful learning at the elementary school level, especially for first grade students who were in the early stage of language development. This study aimed to (1) describe the importance of reading and writing literacy for first-grade students, (2) analyze the factors influencing students’ reading and writing literacy, and (3) identify teachers’ strategies to foster reading and writing literacy among first-grade students. The study employed a descriptive qualitative method with a library research design. Data were obtained from scientific articles and journals published between 2021 and 2025 that were relevant to the topic of reading and writing literacy. The data analysis technique used content analysis, which included data reduction, classification, interpretation, and verification. The results showed that reading and writing literacy played a crucial role in building the foundation of students’ critical, creative, and communicative thinking skills from an early age. Factors influencing literacy development included internal factors such as motivation, reading interest, and cognitive ability, as well as external factors such as family support, teachers’ guidance, and a literate learning environment. The effective strategies to promote literacy were the 15 minute reading activity before lessons, the provision of classroom reading corners, the use of illustrated media and contextual writing activities, and collaboration between teachers and parents in home literacy practices. Through well planned, engaging, and sustainable strategies, students’ reading and writing literacy skills could develop optimally as a foundation for lifelong learning success.